2006
DOI: 10.1007/s10211-006-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Lunar-related reproductive behaviour in the badger (Meles meles)

Abstract: Cyclicity in behaviours, including reproduction, in relation to the lunar cycle is widely documented in some phyla, but weak or unknown in Class Mammalia. In this paper we present long-term video surveillance data of wild Eurasian badgers Meles meles, which reveal a strong correlation between reproductive behaviour and the lunar cycle. Squat marking and raised-leg urination, which increase in frequency at times of reproductive activity, showed maxima around day 22 of the lunar cycle (i.e. new moon). These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Some nocturnal terrestrial animals alter their behaviour and activity with changing light conditions in connection with the lunar cycle, this pattern being presumably shaped by antipredatory strategies (e.g. Daly et al, 1992;Julien-Laferrière, 1997;Brooke et al, 2000;Dixon et al, 2006;Campbell et al, 2008). For mammals and birds the lunar periodicity of behaviour is well studied (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some nocturnal terrestrial animals alter their behaviour and activity with changing light conditions in connection with the lunar cycle, this pattern being presumably shaped by antipredatory strategies (e.g. Daly et al, 1992;Julien-Laferrière, 1997;Brooke et al, 2000;Dixon et al, 2006;Campbell et al, 2008). For mammals and birds the lunar periodicity of behaviour is well studied (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the reproductive cycles of fish, birds, amphibians, and mammals correlate with the lunar phase [20,21,22,23,24]. In terms of an evolutionary meaning, fish may have more success when producing eggs at a time that other animals are also in a reproductive condition [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nights around the new moon period may influence the retinal circadian physiology and photoreceptor adaptation to darkness in lunar‐synchronized animals. On the other hand, “brightness at night” around the full moon period helps with early awareness and discrimination of counterparts or prey/predators, and alters reproductive and foraging behaviors, respectively, with a lunar‐cyclic pattern in certain mammals (Morrison, ; Wolfe and Summerlin, ; Gannon and Willig, ; Dixon et al, ). These field studies suggest that the behavior patterns of wild mammals are affected by periodical changes in the intensity of moonlight.…”
Section: Discussionmentioning
confidence: 99%